La ideología del hablante nativo en la enseñanza de idiomas: una revisión del estado de la cuestión - Yancce, Ruth (2024)
In this article, a synthesis of the state of the art of the most relevant research in relation to native speaker ideology in language teaching is presented. Pioneering research on this topic defined the native speaker ideology and studied how this ideology originates through the native speaker/non-native speaker dichotomy, and identified the main discourses associated with it. The most recent studies focus on the implications of this ideology in the organization and control of the beliefs and perceptions that shape the linguistic attitudes of students, teachers and recruiters towards native and non-native foreign language teachers. This narrative review aims to compare the state of research on this topic in foreign language teaching.